Pengaruh Motivasi Kerja Dan Kompensasi Terhadap Perilaku Etis Karyawan Dalam Sistem Penggajian Dengan Gaya Kepemimpinan Sebagai Variabel Moderating - Daniel Nababan (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
This research is done to analyze the influence of Work Motivation andCompensation toward Employees’ Ethical Behavior within Payroll System by UtilizingLeadership Style as Moderating Variable. This research used 34 people as sample, whowere the employees of PT. Telkom Indonesia Yogyakarta Local Area, with WorkMotivationPayroll,and Leadership Style serving as variables. The hypothesis in thisresearched was tested by using double regression analysis system. The result of thisresearch is that Work Motivation and compensation given brought significant impact inemployees’ ethical behavior within the payroll system, that moderation in leadership stylebrought significant impact within the influence ofwork motivation and compensationtoward employees’ ethical behavior within payroll system, while moderation in leadershipstyle did not brought significant impact within the influence of compensation towardemployees’ ethical behavior within payroll system.